2000
DOI: 10.1017/s1355838200000297
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interference in Trypanosoma brucei by heritable and inducible double-stranded RNA

Abstract: The use of double-stranded RNA (dsRNA) to disrupt gene expression has become a powerful method of achieving RNA interference (RNAi) in a wide variety of organisms. However, in Trypanosoma brucei this tool is restricted to transient interference, because the dsRNA is not stably maintained and its effects are diminished and eventually lost during cellular division. Here, we show that genetic interference by dsRNA can be achieved in a heritable and inducible fashion. To show this, we established stable cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 21 publications
8
128
0
Order By: Relevance
“…In Vivo Depletion of IF2 by RNAi-Due to the availability of a tightly controlled tetracycline-inducible expression system (29), RNAi has become the method of choice to disrupt gene function in T. brucei (22,23). Thus, to investigate the function of IF2 by RNAi, we prepared a construct that contained a defined sequence of the IF2 gene in the sense, as well as the antisense, direction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Vivo Depletion of IF2 by RNAi-Due to the availability of a tightly controlled tetracycline-inducible expression system (29), RNAi has become the method of choice to disrupt gene function in T. brucei (22,23). Thus, to investigate the function of IF2 by RNAi, we prepared a construct that contained a defined sequence of the IF2 gene in the sense, as well as the antisense, direction.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of tetracycline, the RNA was expressed and formed a stem loop that eventually led to the specific degradation of the IF2 mRNA. There have been two types of stuffer sequences used in stem loop constructs, one of trypanosomal origin as described previously (22) and another one of mouse origin (23). Surprisingly, it was shown that the efficiency of RNAi was generally higher when the mouse sequence was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of Lsm proteins was silenced by the two approaches. The Lsm8 was silenced by producing dsRNA in the form of a stem-loop structure, as described under "Experimental Procedures" (35,37). For silencing the Lsm3 gene, PCR was used to amplify the gene that was cloned into the pZJM vector carrying the two T7 opposing promoters (35).…”
Section: Fig 4 the Level Of Sl Rna And The Y-structure Intermediatementioning
confidence: 99%
“…Regulatable TbMP48 sequences to produce interfering dsRNAi were introduced into both the bloodstream and procyclic stage cell lines, as described (Shi et al 2000;Wang et al 2000). We were unable to produce null mutants of TbMP52 and thus produced mutant BFs in which we introduced a regulatable TbMP52 allele and then deleted both endogenous alleles in BFs as described by Wirtz et al (1999).…”
Section: Functions Of Editing Complex Componentsmentioning
confidence: 99%